ナンキョク ショウワキチ ニ オケル タテモノ シュウヘン ノ ユキ ノ フキダマリ ト フウソク エンチョク ブンプ ノ ジッソク - 三橋, 博巳; ミツハシ, ヒロミ; Mitsuhashi, Hiromi (1982)
P(論文) 第19次南極地域観測隊に参加して, 昭和基地主要部の実在高床式建物(観測棟・電離棟)周辺に形成されるスノードリフトの形態ならびに吹溜量について測定を行った。また主に強風時を対象とし, 建物近傍での粗度長やべき指数を求め風速鉛直分布特性の検討を行った。実測結果から次のことが得られた。(1)高床式建物周辺に形成されるスノードリフトの形態は, 建物周辺にウィンドスクープを形成し, 風下側の形態は鋭い稜線を持つ馬蹄型となった。また1年間の吹溜量を風下側測定区間で求めると, 観測棟では78.3m^3,電離棟では181.7m^3となった。(2)風速鉛直分布特性は比較的対数則に従った。対数則より求めた粗度長Z_0は10^0～10^<-4>(m)の範囲で平均値は2.2×10^<-2>(m)となった。べき指数αは1/2.9～1/7の範囲で平均値は1/4.9となった。 The author joined in the 19th Japanese Antarctic Research Expedition and measured the forms and quantities of snowdrifts accumulated around the existing high floor huts (Observation Hut and Ionosphere Hut) located in the major part of Syowa Station. He also investigated the characteristics of the wind profile near the huts selectively on days when strong wind was blowing by obtaining the roughness length and power index of mean wind profile on the snow-covered ground. The results of measurement are summarized as follows : (1) The snowdrifts around the high floor huts formed a wind-scoop and changed into U type with a sharp ridge line on the lee side. The annual cumulative quantities of snowdrifts, measured in the measuring section on the lee side, were 78.3m^3 and 181.7m^3 around Observation Hut and Ionosphere Hut respectively. (2) The characteristics of the wind profile conformed to the logarithmic law comparatively. The roughness length, Z_0,was in the range from 10^0 to 10^<-4> with 2.2×10^<-2>(m) as the mean value. The power index α ranged from 1/2.9 to 1/7 with 1/4.9 as the mean value. departmental bulletin paper